DETERMINAN KEPATUHAN PAJAK PADA WAJIB PAJAK ORANG PRIBADI YANG MELAKUKAN PEKERJAAN BEBAS: DALAM KERANGKA THEORY OF PLANNED BEHAVIOR DAN BUDAYA PAJAK - Dasapradani, Nadya Septy (Jurnal Ilmiah Mahasiswa FEB, 2018)
This study aims at examining the influence of planned behavior theory and tax culture on tax compliance. The determinants to be evaluated consist of attitudes, subjective norms, and behavioral controls perceived, as well as tax culture variables. 100 individual taxpayers who perform independent work in Malang are selected as the respondents through convenience sampling method. This quantitative research applies field study or survey method, i.e. directly observe the research object by visiting the individual taxpayers in Malang. The data are analyzed using Partial Least Square through SmartPLS. The results of this study indicate that the attitude and subjective norms positively influence tax compliance, while the control of perceived behavior and tax culture do not show any effect on tax compliance.Keywords : Planned Behavior Theory, Tax Culture, Tax Compliance,Independent Worker